Effect of deposition regime transition on the properties of Al:ZnO transparent conducting oxide layer by radio frequency magnetron sputtering system - Abd Rahman M.N.; Zuhdi A.W.M.; Amirulddin U.A.U.; Isah M.; Azman N.I.; Arsad A.Z.; Arzaee N.A.; Mansor M.; Shuhaimi A. (Elsevier Ltd, 2025)
High-quality zinc oxide thin films doped with aluminium adatoms have effectively been fabricated on pristine soda-lime silica glass substrates via radio frequency magnetron sputtering system. The deposition temperature was varied to explore the impact of deposition regime transition of as-deposited Al:ZnO thin films on their performance as transparent conducting oxide layers. In particular, the depositions were conducted at room temperature, 100 C, 200 C, and 300 C, allowing for a comprehensive assessment of the resulting films. The Raman spectra depicted the modulation of Raman bands in correlation with the deposition regime transition, illustrating the impact of thermal induction on various properties of the as-deposited aluminium-doped zinc oxide thin films. Atomic force microscopy reveals the transformation from nearly spherical to elongated shape structure was obtained as the deposition process shifted from kinetic limited to thermodynamic limited regimes. The phase analysis and grazing incident of x-ray diffractometer disclose a single crystal orientation has been achieved at thermodynamic limited regime. However, two different crystal planes were predominant comparing between the surface and structural of as-deposited aluminium-doped zinc oxide thin films. It is also evident that a highly transparent with low lattice strain and better carrier concentrations of as-deposited aluminium-doped zinc oxide thin films were realized at thermodynamic limited regimes. ? 2024 Elsevier Ltd and Techna Group S.r.l.